90.1k views
5 votes
Perform the indicated operation and write the result in the form a + bi.
(4 + 9i) (7-4i)

User WillD
by
5.3k points

2 Answers

2 votes

Answer:

-10 - 4i

Explanation:

This is the correct answer.

User Lostphilosopher
by
5.6k points
6 votes

The result of (4 + 9i)(7 - 4i) in the form of a + bi is 64 + 47i.

Solution:

Given, product term is (4 + 9i)(7 – 4i )

We have to find the result and write it a + bi form.


\text { Now, }(4+9 i) *(7-4 i)=4 *(7-4 i)+9 i *(7-4 i)

Multiplying the terms we get,


=4 * 7-4 * 4 i+9 i * 7-9 i * 4 i
=28-16 i+63 i-36(i)^(2)

We know that value of
i^2 is -1

= 28 – 16i + 63i – 36(-1)

= (28 + 36) + (63 – 16)i

= 64 + 47i

Hence, the result is 64 + 47i which is in form of a + bi

User BytesGuy
by
5.7k points